Effects of Maternal Deprivation on the Prefrontal Cortex of Male Rats: Cellular, Neurochemical, and Behavioral Outcomes - Poleksic, Joko; Aksic, Milan; Kapor, Slobodan; Aleksic, Dubravka; Stojkovic, Tihomir; Radovic, Marina; Djulejic, Vuk; Markovic, Branka; Stamatakis, Antonios (Frontiers in Behavioral Neuroscience, 2021)
Stressful events experienced during early life are associated with increased vulnerability of developing psychopathology in adulthood. In the present study, we exposed 9-day-old Wistar rats to 24 hour maternal deprivation (MD) with the aim to investigate the impact of early life stress (ELS) on morphological, biochemical and functional aspects of the prefrontal cortex (PFC), a brain region particularly sensitive to stress. We found that in superficial medial orbital cortex (MO), young adult male rats had reduced density of GAD67 and CCK immunopositive cells while the rostral part of ventral lateral orbital cortex (roVLO) showed a decrease in the density of GAD67 immunopositive cells in both superficial and deep layers. In addition, superficial rostral part of area 1 of the cingulate cortex (roCg1) and deep prelimbic cortex (PrL) were also affected by MD indicated by the reduction in PV immunopositive cellular density. Furthermore, MD induced an upregulation of BDNF, while it did not affect the overall expression of Iba1 in neonatal or young adult PFC as measured by Western blot, however a microglial activation in young adult MD rats was detected immunohistochemically in deep layers of MO and infralimbic cortex (IL). Interestingly, when young adult male rats were subjected to a behavioral flexibility test in a T-maze, MD rats showed a subtle impairment in T-maze reversal learning indicating a mildly affected PFC function. Taken together, our findings demonstrate that MD reduces the density of interneurons and induces microglial activation in particular PFC areas at young adulthood and may alter synaptic plasticity accompanied by PFC dysfunction.